Should We Repair the Pronator Quadratus in a Distal Radius Fracture with an Ulnar Styloid Base Fracture? A Biomechanical Study - Maniglio, Mauro; Truong, Victor; Zumstein, Matthias; Bolliger, Lilianna; McGarry, Michelle H.; Lee, Thay Q. (Journal of Wrist Surgery, 2021)
Background Merits of repairing the pronator quadratus (PQ) to restore distal radioulnar joint (DRUJ) stability after a volar approach remain controversial. Distal radius fractures are often associated with ulnar styloid fractures (USF). When involving the fovea, this USF can lead to a DRUJ instability. The PQ repair may be key in reducing this DRUJ instability.Methods This study aims to assess the biomechanical role of PQ repair in a cadaveric model of USF. In 17 forearm specimens, a USF including the fovea was executed. Positional changes of the DRUJ in forearm rotation and dorso-palmar (DP) translation were measured with variable loads (0, 2.5, and 5N) applied to the PQ origin.Results Forearm rotation and DP-translation decreased significantly with PQ loading of 5N, changing on average by 5 degrees and 0.6 mm, respectively.Conclusion We found a significant decrease in forearm rotation and DP-translation comparing a fully loaded PQ to an unloaded PQ in our cadaveric model.
Keywords: distal radio-ulnar joint; distal radio-ulnar ligaments; distal radius fracture; pronator quadrates; ulnar styloid fracture